Strategi Kepemimpinan Kepala Madrasah dalam Membangun Budaya Disiplin di Era Kurikulum Merdeka - minan khoiron; Nur Fatih Ahmad; Achmad Dany; Ahmad Afrizal Rizqi; Muhammad Najib (Pascasarjana Universitas Qomaruddin, 2025)
This study aims to examine the role and leadership strategies of the principal in improving student discipline at MTs Al Hidayah Serah Panceng, Gresik, within the context of implementing the new curriculum and character strengthening policies. The dual mandate of madrasahs to develop both competence and character—based on the Decree of the Minister of Religious Affairs (KMA) No. 450 of 2024 and the Character Education Strengthening Program (PPK)—requires an adaptive leadership model. This research employs a qualitative approach with a case study method. Data were collected through in-depth interviews, participatory observation, and document analysis, and analyzed using Miles and Huberman’s interactive model. The findings reveal that the principal’s leadership (H. Asykuroni) is integrative, combining charismatic, democratic, strategic, and cultural styles. The discipline enhancement strategy emphasizes inner control through personal example and cooperative control through collaboration with parents, while external control based on the reward–punishment system is not the dominant approach. The most original finding is the practice of “collaborative learning module development,” which synthesizes the guidelines of LP Ma’arif NU and the Ministry of Religious Affairs. This innovation represents a bottom-up implementation of the Projek Penguatan Profil Pelajar Pancasila dan Rahmatan lil ‘Alamin (P5RA) philosophy. The study concludes that adaptive leadership grounded in local wisdom and human resource empowerment successfully fosters a discipline culture based on moral awareness, and serves as an effective model for harmonizing national education policies with the cultural–religious identity of madrasahs.